Odpowiedzi

Najlepsza Odpowiedź!
2010-03-09T14:51:57+01:00
X-y-=2
2x+y=4
x=2+y
2x+y=4
x=2+y
2(2+y)+y=4
x=2+y
4+2y+y=4
x=2+y
3y=4-4
x=2+y
3y=0/:3
x=2+y
y=0
x=2+0
y=0
x=2


x+2y=0
-x+y=-3
x=0-2y
-x+y=-3
x=-2y
-x+y=-3
x=-2y
2y+y=-3
x=-2y
3y=-3/:3
x=-2y
y=1
x=-2*1
y=1
x=-2
Daj naj;)
2010-03-09T15:06:10+01:00
X-y =2
2x+y=4
x = 2 + y
2x + y = 4
x = 2 + y
2 * (2 + y) + y = 4
x = 2 + y
4 + 2y + y = 4
x = 2 + y
3y = 0
x = 2 + y
y = 0
x = 2 + 0
y=0
x=2


x+2y=0
-x+y=-3
x+2y=0
y= -3 + x
x+2 * (-3 + x) =0
y= -3 + x
x+ (-6) + 2x = 0
y= -3 + x
3x = 6
y= -3 + x
x = 2
y= -3 + 2
y=-1
x = 2


Rozwiązanie na pewno jest poprawne :)